In Pursuit of New Imprinting Syndromes by Epimutation Screening in Idiopathic Neurodevelopmental Disorder Patients. (27th May 2015) - Mayo, Sonia; Monfort, Sandra; Roselló, Mónica; Oltra, Silvestre; Orellana, Carmen; Martínez, Francisco
Abstract : Alterations of epigenetic mechanisms, and more specifically imprinting modifications, could be responsible of neurodevelopmental disorders such as intellectual disability (ID) or autism together with other associated clinical features in many cases. Currently only eight imprinting syndromes are defined in spite of the fact that more than 200 genes are known or predicted to be imprinted. Recent publications point out that some epimutations which cause imprinting disorders may affect simultaneously different imprinted loci, suggesting that DNA-methylation may have been altered more globally. Therefore, we hypothesised that the detection of altered methylation patterns in known imprinting loci will indirectly allow identifying new syndromes due to epimutations among patients with unexplained ID. In a screening for imprinting alterations in 412 patients with syndromic ID/autism we found five patients with altered methylation in the four genes studied: MEG3, H19, KCNQ1OT1, and SNRPN . Remarkably, the cases with partial loss of methylation in KCNQ1OT1 and SNRPN present clinical features different to those associated with the corresponding imprinting syndromes, suggesting a multilocus methylation defect in accordance with our initial hypothesis. Consequently, our results are a proof of concept that the identification of epimutations in known loci in patients with clinical features different from those associated with known syndromes will eventually lead to the definition of new imprinting disorders.